Promoting Metacognitive Listening Strategy through Task-based Approach in the Teaching of Listening - Zuhro, Putri Fatimatuz (Universitas Negeri Surabaya, 2022)
Listening is an essential skill in learning a foreign language since it may support the learners in understanding the input and their language development. However, the students faced some difficulties in mastering their listening skills. The teacher needs to support the students by implementing the right approach and giving them a suitable listening strategy. One of the listening strategies that might help students control their learning and solve their problems is metacognitive listening. Moreover, task-based approach is one of the approaches that aid the teacher in promoting a metacognitive listening strategy. Focusing on a task-based approach and metacognitive listening strategy, this study aims to determine whether implementing a task-based approach can help the students understand how to use metacognitive listening strategy. The study was conducted with a case study as the research design. In addition, the data of this study were collected through interview and observation. The participant of this study was the teacher in one senior high school in Gresik. The data showed that implementing a task-based approach is beneficial for promoting the use of metacognitive listening strategy for senior high school students.